CHORAL ACTIVITY IN RĂHĂU, ALBA COUNTY - ŞUŞMAN, Dragoş Ioan (Studia Universitatis Babes-Bolyai Musica, 2013)
The present study takes a journey into the musical life of Romanians in Răhău, a village on the outskirts of Sebeş, studying their choral activity during the first half of the 20th century. The material is entirely based on documents from the Răhău Orthodox Parish fund at the Romanian National Archives, Alba County Service. The information that is to be presented focuses on three aspects of the musical life in the above mentioned village: the choral activity of the students of the Orthodox confessional school, that of the church choir and that of the Sfântul Gheorghe Society choir. As the documentary references are not sufficiently extensive to allow for the separate treatment of the three subjects, we will only mention them chronologically.